Gaya Desain Pada Interior Gereja Katolik Santo Albertus Magnus Jetis Yogyakarta - Tanuwidjaja, Laurentius (Intra, 2013)
Stylish design shows a shape, characteristic, expression, behavior and human culture that produces a new idea or thought about the concept of style in artifact factors. Catholic Church St. Albertus Magnus in Jetis Yogyakarta is one of the works YB Mangunwijaya. This church building reflects the simple and open but still retain the details that contain profound meaning of the traditional values of local cultures. This study uses qualitative research. Collecting data through interviews, literature review and field observations. The data were analyzed descriptively, the aim to determine the extent of the application of interior design styles on Church St. Albertus Magnus Jetis both in the field of space-forming elements (floors, walls and ceiling), transition elements (windows, doors and ventilation), a space filler elements (furniture), symbols, and decorative elements. From these results it was concluded Design of this church still thick with the feel of Java but still guided by the provisions of the church building, according to the design style of the concept of Romo Mangun who make the Church a simple and not extravagant but still true to the design, the church is also inculturation cultural experience. Inculturation of the church with the local culture. Inculturation seen from the laying of the building, forming elements of space and space filler. While the design style of Romo Mangun visible from space forming element, the element of space filler and natural materials.